James Clavell's Noble house [videorecording (DVD)] - Brosnan, Pierce; Clifford, Michael; Nelson, Gary, 1934-; Bercovici, Eric; Raffin, Deborah; Masters, Ben; Rhys-Davies, John; Nickson, Julia; Dhiegh, Khigh; Jackson, Gordon, 1923-1990; Kwouk, Bert; Kwan, Nancy, 1939-; et al. (Lionsgate, 2008)
Ian Dunross is named 'Tai-Pan' (Supreme leader) of the powerful British-East Asia trading company, Struan & Co. His rival is attempting a hostile takeover. Suddenly plunged into a criminal underworld of international espionage, deception and financial crises, Dunross turns up the heat by engaging in a dangerous romance with his nemesis's aide. Danger lurks around every corner and Dunross ultimately sees he has no choice but to fight for his company's honor and survival.